Investigation of Aloe vera mediated ZnO-β-CD nanocomposite for photocatalysis and antimicrobial applications - Arti Hadap; Vishal R. Panse; Serhii Tereshchuk (Scientific Reports)
Abstract This study presents the green synthesis of an Aloe vera based ZnO-β-cyclodextrin (β-CD) nanocomposite for photocatalysis and antimicrobial applications. UV-Visible spectroscopy, Fourier transform infrared (FTIR), X-ray diffraction (XRD), Field emission electron microscopy (FESEM), and band gap energy measurement, were employed to investigate the optical and structural features. Due to unique bandgap (3.0 eV) and enhanced electron-hole recombination dynamics, the newly synthesized nanocomposite can not only able to demonstrate the efficient photocatalytic degradation of methylene blue (MB) dye by achieving complete discoloration at 6 pH within 160 min under visible light—a significant improvement over previously reported ZnO-based system, but furthermore, it also strongly combatted by the antibacterial activity against Gram-positive bacteria S. aureus, gram-negative bacteria E. coli, and the fungus strain A. niger. This is due to the generation of singlet oxygen (O2*–) and hydrogen oxide radical (–OH*) in presence of light and air, which inhibit the growth of cells of bacterial and fungal strains. Notably, the nanocomposite was biocompatible, posing minimal cytotoxicity to healthy cells, making it a promising candidate for environmental and biomedical application.